KOMUNIKASI POLITIK ANGGOTA DPRD PROVINSI SUMATERA BARAT DALAM MEMPERJUANGKAN ASPIRASI MASYARAKAT - Lisa Kurnia; Sarmiati Sarmiati; Ernita Arif (Ensiklopedia of Journal, 2022)
Members of the DPRD of West Sumatra Province have a moral responsibility to fight for the aspirations of the community. In fighting for the aspirations of the community, political communication is needed ideally to give a better influence on the community. In fighting for the aspirations of the community, it is necessary for the members of the council to have good political communication skills. This study aims to analyze the experience of political communication of members of the DPRD of West Sumatra Province in fighting for aspirations in their constituency and to analyze the essential meaning of the experience of political communication of DPRD members in fighting for the aspirations of the people in their constituency. The research method used is a qualitative phenomenological approach with a constructivist paradigm. With data collection techniques through in-depth interviews, observation, and documentation. The results of the research obtained are that the communication that occurs is dialogical which allows anyone, from politicians, activists, and partners to become communicators and communicants at almost the same time. The aspirations conveyed by the community are the main messages in political communication that occur throughout the struggle for the aspirations of the people by members of the DPRD of West Sumatra. Mass communication, interpersonal communication, and organizational communication are communication channels used throughout the agenda for the struggle for community aspirations by members of the DPRD of West Sumatra Province. The obstacles encountered in fighting for the aspirations of the community are the existence of changing regulations, and the need for synchronization of regulations from the central government, city district governments, and provincial governments related to the authority of the aspirations submitted and synchronization with the work programs of relevant agencies and the RPJMD, with a long period of 1 year. making it difficult to fight for urgent aspirations.Keywords: Communication, Politic, DPRD, Aspirations.